Home delivery complicated with puerperal sepsis in urban India - Chavan, Niranjan N.; Changede, Pradnya R.; Khan, Shaista R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Puerperal sepsis is among the leading and preventable causes of maternal morbidity and mortality worldwide and especially in developing countries. We report an interesting case of home delivery complicated with puerperal sepsis, who required obstetric hysterectomy. Inspite of being a resident of an urban metropolitan city patient had no access to antepartum, intrapartum or even postpartum care. She presented on day eleven postpartum to our institute by which time, her condition had progressed to frank pyoperitoneum and severe anaemia. Urgent, aggressive intervention in the form of evacuation of intra-abdominal pus, obstetric hysterectomy with oophorectomy saved her life.